A dual-mode polarization image sensor design based on in-pixel dual-band metal wire grid for trustworthy sensing - Zheng, Hongxia (2024)
In this article, we present the design of an on-chip polarization image sensor with a hardware root of trust (RoT) for trustworthy sensing provided by an interconnection metal-wire-grid (MWG) structure using a standard complementary-metal-oxide-semiconductor (CMOS) process. The proposed MWG structure features dual operation modes, which are polarization image sensing mode at the visible spectrum and physical unclonable function (PUF) mode at the near-infrared spectrum. By integrating the MWG on top of the photo-sensing pixel, the corresponding photocurrent is read out with a mainstream three-transistor-active-pixel-sensor (3T-APS). Moreover, prototype chips are fabricated using a 65-nm 1P8M CMOS process to validate the proposed design. For the polarization mode at 630 nm, the extinction ratio (ER) is measured to be 17 dB. For the PUF mode at 875 nm, the averaged unstable bits and bit error rate (BER) of 15 test chips are reported to be 3.5% and 0.29%, respectively. The responses generated in the PUF mode of the fabricated sensor chips also passed the widely adopted National Institute of Standards and Technology (NIST) and the autocorrelation function (ACF) randomness tests.